2017
DOI: 10.30877/ijmh.4.4.2017.391-395
|View full text |Cite
|
Sign up to set email alerts
|

Own a Pet – Stay well and Happy : an exploratory study

Abstract: Background: Pets seem like perfect companions providing unconditional love without any expectation from owner. Pets can be seen as stress reducer and being looked upon as companions and members of the family. The purpose of this study was to examine the effect of pet ownership on happiness, psychological well-being in pet owners and non-pet owners. Methodology: Data was collected from 100 participants. Data was gathered by means of questionnaires that assessed happiness, psychological well-being. The Ryff scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The findings of the current study revealed a significant difference in the psychological well-being of individuals who keep pets compared to those who do not own pets. The research showed that pet keepers tend to have higher levels of psychological wellbeing than non-pet keepers, aligning with the results of a study conducted by Chaudhary and Srivastava (2017), which also reported that pet owners experience enhanced psychological well-being compared to individuals without pets.…”
Section: Discussionsupporting
confidence: 84%
“…The findings of the current study revealed a significant difference in the psychological well-being of individuals who keep pets compared to those who do not own pets. The research showed that pet keepers tend to have higher levels of psychological wellbeing than non-pet keepers, aligning with the results of a study conducted by Chaudhary and Srivastava (2017), which also reported that pet owners experience enhanced psychological well-being compared to individuals without pets.…”
Section: Discussionsupporting
confidence: 84%